The role of TLR-2 and TLR-4 gene polymorphisms in the development of sepsis in children with severe burns - Koval, M.; Sorokina, O. (Journal of Education, Health and Sport, 2022)
Recently, many studies are based on the study of innate immunity genes, namely the role of TLRs in the development of various diseases. Severe burn injury is characterized by the development of hyperimmune reactions, which further leads to the development of multiple organ complications and sepsis. The aim of our study was to identify the frequency and prognostic value of polymorphism of TLR-2 Arg753Gln and TLR-4 Thr399 Ile genes and their role in the development of sepsis and MOD in children with severe burns. Materials and methods: genetic analysis of TLR-2 Arg 753 Gln and TLR-4 Thr399 Ile gene polymorphisms was performed in children with severe and extremely severe burns (n ​​= 22) who were treated in the anesthesiology department with intensive care beds. Results: as a result of the obtained data, the heterozygous genotype TLR-2 Arg 753 Gln was detected in 69.5% (n = 16), in 31.8% (n = 7) patients with burn injury polymorphism was not detected. In 13.6% (n = 3) cases, polymorphism was associated with sepsis and MOD. Sepsis and normal homozygous genotype were diagnosed in 4.5% (n = 1). Heterozygous genotype TLR-4 Thr399 Ile was observed in 18.2% (n = 4) patients, of which only 4.5% (n = 1) patients had polymorphism associated with sepsis and MOD. Analysis of the association of TLR 2 genotypes and markers of acute inflammation revealed statistically significant differences between the heterozygous TLR 2 Arg 753 Gln genotype and C-reactive protein (CRP) levels in the blood of patients on day 3 of burn disease. Conclusions: The study of the role of innate immune system genes is promising in predicting the development of sepsis and complications in severe burns and requires further careful study.